PENGARUH SOCIAL MEDIA MARKETING, BRAND IMAGE DAN BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN SCARLETT WHITENING - Indriani, Lisma; Harahap, Kartini (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2024)
Customer decision in selecting and purchasing a particular brand are influenced by various factors like social media marketing, brand image, and brand awareness. This study is focused on examining how social media marketing, brand image, and brand awareness impact the decision-making process for purchasing Scarlett Whitening products. The research employs a quantitative methodology with an associative approach. Data analysis involves testing for validity, reliability, classical assumptions, multiple linear regression, and hypothesis testing. The study's results indicate that social media marketing, brand image, and brand awareness each have a positive and significant impact on purchasing decisions for Scarlett Whitening products, both independently and together.